META ANALISIS: PENGARUH FAKTOR-FAKTOR FRAUD DIAMOND TERHADAP F-SCORE - Putra, Wilxen Sanjaya; Pricilya, Zuliet -; -, Sukmawati -; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
This research aims to prove the influence of the fraud diamond factors on the F-score. Fraud Diamond is a concept that discusses the reasons and factors why fraud can occur in a company's financial statements. In this study, a meta-analysis study method approach was used in hypothesis testing. In this study, a sample of 30 articles was obtained which met the criteria to be used as research materials, the samples obtained were from previous research conducted from the 2010-2022 period which is still related to diamond fraud. The sample search uses an application media called Public of Perish (PoP) and also uses a tool called Google Scholar which is directly related to the Public of Perish (PoP). Then the sample selection was used by purposive sampling method. The results of the research analysis show that the four independent variables tested after being transformed into r and various procedures according to the meta-analysis step prove that they have a significant positive effect which means that all variables have been proven to have a significant effect on the F-score.